Role-play or debate to promote students' argumentation and justification on an issue in animal transgenesis - Simonneaux, Laurence (International journal of science education, 2001)
This paper compares the impact of a role-play and a conventional discussion on students' argumentation on an issue involving animal transgenesis. Students were confronted with an imaginable but fictional situation. They had to decide whether or not to approve a giant transgenic salmon farm being set up in a seaside village. Students received the same teaching and information, the only differences being in the debate situation. Students were asked to reach a decision on well-argued grounds, to identify areas of uncertainty and to define the condition or conditions under which a change of view might be considered. They had to write them down. Pre- post-tests were used to assess the students' opinions. The role-play and discussion were all video- and audio-taped and transcribed in full. The analysis focuses on the argumentative structure of the students' discourse and identifies the reference areas that students draw on to deliver their arguments. The theory of economics of 'greatness' or 'importance', which has recently emerged as a framework for the sociology of justification, has also been used in analysing students' discourse.